Technology strategy for the automotive industry the case study of Motorix Motor Sales, Inc. - Ching, Laurence Y. (Technology Management Center, 2007)
In the increasing competitiveness in the automotive industry in the Philippines, companies have changed and adopted the way they do business. Consumer markets are become more complex and more diverse. Competition has become more tight as more automotive companies and auto shops have entered the playing field. To be ahead of the pack, certain companies allocate resources, investing on new ad better technology to further improve their operational efficiency and its quality of service. In the year 2005, Motorix Motor Sales Incorporated (MMSI) thought of embarking on a project that they hoped would significantly provide them a technology strategy and enhance their business value. The project aims to provide management a better assessment of the current situation of the company. This would provide adequate information to enable management to formulate a technology strategy and gaining competitive advantage. The project will concentrate mainly on the service department of the company from which most of the technology are being used. This project will provide an opportunity to assess service division on which direction they should go. Utilizing their knowledge assets and maintaining their best practices. Providing enough information in helping in making the best decision on which technology and service upgrade would suit them in reaching their objectives. Interviews will be conducted with vital person in the industry like service manager, shop owners, analysis, specialist and end-users to obtain in depth information. Survey will be done in different area to be able to get a majority of sample. Focus group discussion will be conducted to obtain additional information. Internet and library research will also be done to help provide additional information for the project. The key success factors in this project include the honesty and cooperation of the interviewees, FGD group and the surveying publics. Time allotment will also be crucial in this project due to the wide areas of coverage of samples that will be taken for the survey that will be taken. Management support and involvement is also important in for its success. Once the project is completed, it will produce important information that would contribute value to the company's objectives, identify its strengths and weakness and be able to make recommendations that would best suit the company in moving forward to the next level.